2018
DOI: 10.2147/cia.s149038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flat and textured insoles on the balance of primary care elderly people: a randomized controlled clinical trial

Abstract: BackgroundAging is associated with reduced postural stability and increased fall risk. Foot orthoses have been reported as an adjuvant intervention to improve balance by stimulating foot plantar mechanical receptors and thus increasing somatosensory input.PurposeThe aim of this study is to evaluate the effect of flat and textured insoles on the balance of primary care elderly people.DesignProspective, parallel, randomized, and single-blind trial.MethodsA total of 100 subjects from a primary care unit, aged ≥65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…Some studies found improvements in postural control during static balance using soft textured insoles made in Evalite Pyramid EVA (Kenny et al 2019b ) or rigid textured surface made from plastic floor matting material (Corbin et al 2007 ; Annino et al 2015 ; Vieira et al 2017 ) in healthy young subjects. Other studies used soft (Hatton et al 2011 ; de Morais Barbosa et al 2018 ), semi-rigid (Palluel et al 2008 ), and rigid materials (Palazzo et al 2015 ; Annino et al 2018 ) to investigate postural stability in elderly people finding different results about analyzed postural parameters. Palluel et al ( 2008 , 2009 ) investigated the effects of sandals equipped with spike insoles, finding no immediate effects, but an improvement of postural control after 5 min standing or walking in elderly and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found improvements in postural control during static balance using soft textured insoles made in Evalite Pyramid EVA (Kenny et al 2019b ) or rigid textured surface made from plastic floor matting material (Corbin et al 2007 ; Annino et al 2015 ; Vieira et al 2017 ) in healthy young subjects. Other studies used soft (Hatton et al 2011 ; de Morais Barbosa et al 2018 ), semi-rigid (Palluel et al 2008 ), and rigid materials (Palazzo et al 2015 ; Annino et al 2018 ) to investigate postural stability in elderly people finding different results about analyzed postural parameters. Palluel et al ( 2008 , 2009 ) investigated the effects of sandals equipped with spike insoles, finding no immediate effects, but an improvement of postural control after 5 min standing or walking in elderly and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Qu [29] did not observe any difference in static stability but reported that rigidity of the insole could improve the participant's mobility. De Morias Barbosa et al [30] have shown that using both textured and smooth insoles in older people with normal plantar sensation could immediately improve the dynamic balance measured with TUG. The results of the literature mentioned above are in line with the findings of our study and indicate that the textured insoles do not immediately change the postural sway of older people with normal plantar sensation (although they could improve the mobility of the users).…”
Section: Discussionmentioning
confidence: 99%
“…The other factors affecting static standing balance include toe muscle strength10 ) and plantar sensation11 ) . In addition, the insoles reportedly improve body sway12 ) . A previous report has shown that a textured insole is more effective in stabilizing the posture than a flat insole suggesting that insole surface shape affects static balance13 ) .…”
Section: Discussionmentioning
confidence: 99%